Does ethnic-racial identity modify the effects of racism on the social and emotional wellbeing of Aboriginal Australian children? - Macedo, Davi M; Smithers, Lisa G; Roberts, Rachel M; Haag, Dandara G; Paradies, Yin; Jamieson, Lisa M (My University, 2019)
This study investigates the protective role of ethnic-racial identity (ERI) affirmation on the longitudinal association between racism and Aboriginal Australian children's social and emotional well-being (SEWB). 408 children from the K-Cohort of the Longitudinal Study of Indigenous Children were included in the analysis. Data were collected through questionnaire-guided interviews at 7-10 and 9-12 years of age. Children's racism experience, SEWB (Strengths and Difficulties Questionnaire), and confounding were reported by caregivers. ERI was reported by children and dichotomized into high versus low. Generalized linear models with log-Poisson links and robust errors were used to estimate adjusted Risk Ratios (RRa) for the effect of racism on SEWB domains. Effect-measure modification analysis was used to verify differences on effect sizes per strata of ERI affirmation. The presence of modification was indicated by the Relative Excess Risk due to Interaction (RERI). Slightly above half (51.4%) of the children presented high ERI affirmation. Children exposed to racism and with low ERI affirmation were at increased risk of hyperactive behavior (RRa 2.53, 95% CI 1.17, 5.48), conduct problems (RRa 2.35, 95% CI 1.07, 5.15), and total difficulties (RRa 1.73, 95% CI 0.84, 3.55). Positive RERIs indicated the joint effects of racism and low ERI affirmation surpassed the sum of their separate effects in these domains. Children with high ERI affirmation were at increased risk of peer problems (RRa 1.66, 95% CI 0.78, 3.52). These findings suggest that ERI may mitigate the risk of poor SEWB due to racism. Fostering affirmative ERI can be an important strategy in promoting resilience in Aboriginal Australian children.
Plos one
Keywords: Disadvantage, adversity and resilience; Childhood and child development; Culture and language; Health and wellbeing